The Rhetoric of Reassurance in First John: "Dear Children" Versus the "Antichrist" - Wendland, Ernst R. (Neotestamentica, 2007)
This article approaches the study of "rhetoric" as manifested in John's first epistle from the threefold perspective of form, content, and function. Four primary stylistic features of this letter are singled out for special examination and exemplification: recursion, contrast, focus, and mitigation. These interrelated devices enable the author to enhance his chosen "rhetoric of reassurance" whereby he seeks to strengthen and encourage the community of believers which is being threatened by false teachers. His message, which majors on the three themes of faith, love, and obedience in relation to the central truth about Jesus Christ, the Son of God (3:23), is systematically recycled synonymously for emphasis throughout the discourse. This hortatory-homiletical text is also analyzed in a general way in terms of the principal "speech acts" that it performs in relation to its potential audience, then and now. A concluding section outlines some of the major implications of this distinctive Johannine rhetoric in relation to text analysis, interpretation, and communication (Bible translation, print formatting, and media transposition).
free